Revolutionizing healthcare: the transformative potential of nanotechnology in medicine - Durgam, Lavan K.; Oroszi, Terry L. (Frontiers in Drug Delivery, 2025)
Medical science stands on the brink of transformation thanks to nanotechnology’s fast-paced development, which promises major advancements. Working with materials at the nanoscale within a 1–100 nm range allows scientists to tap into special physicochemical characteristics that open up new possibilities in diagnostics, drug delivery, and regenerative medicine. The review explores nanotechnology’s revolutionary effects on healthcare by highlighting its roles in medical imaging applications and diagnostic procedures, drug delivery systems, tissue engineering, and vaccine development. The design principles of nanomaterials, which encompass synthesis methods alongside functionalization and characterization techniques, are presented here. This review analyzes the impact of artificial intelligence in nanomedicine alongside the enduring effects of nanomaterials and related ethical and safety issues. The review further combines multiple study findings to offer a thorough overview of nanotechnology’s medical applications while suggesting research and clinical translation paths.